International e-Conference on Computer Science 2006 - Simos, Theodore; Psihoyios, Georgios (Lecture series on computer and computational sciences, 2013)
Lecture Series on Computer and on Computational Sciences(LSCCS) aims to provide a medium for the publication of new results and developments of high-level research and education in the field of computer and computational science. In this series, only selected proceedings of conferences in all areas of computer science and computational sciences will be published. All publications are aimed at top researchers in the field and all papers in the proceedings volumes will be strictly peer reviewed. The series aims to cover the following areas of computer and computational sciences: Computer Science Hardware Computer Systems Organization Software Data Theory of Computation Mathematics of Computing Information Systems Computing Methodologies Computer Applications Computing Milieu Computational Sciences Computational Mathematics, Theoretical and Computational Physics, Theoretical and Computational Chemistry Scientific Computation Numerical and Computational Algorithms, Modeling and Simulation of Complex System, Web-Based Simulation and Computing, Grid-Based Simulation and Computing Fuzzy Logic, Hybrid Computational Methods, Data Mining and Information Retrieval and Virtual Reality, Reliable Computing, Image Processing, Computational Science and Education